THE ANALYSIS OF BALANCE SCORECARD TO MEASURE THE PERFORMANCE OF THE HEALTH INSTITUTION (Case Study at UPT X) - Permana, Risda Hadi (Jurnal Ilmiah Mahasiswa FEB, 2016)
In facing the increasingly complex business environment nowadays, it is required a performance measurement method that can assess the institution’s performance accurately and comprehensively such as Balanced Scorecard. It is a performance measurement tool that combines the measurement of the financial and non- financial performance including the perspective of learning and growth, internal business process perspective, customer perspective and financial perspective.This study uses the data of UPT X in 2012-2014. This research is descriptive method which uses a case study approach. Data collection techniques include primary data by distributing questionnaires and secondary data by acquire documentation of the institution and literature related to the research topic.The results of the research conducted have shown that the measurement of performance using  Balanced  Scorecard  at  UPT  X  show  a good  performanceoverall. The advantages and the lacks of the performance of each perspective impact either directly or indirectly for the performance in other perspectives to the financial perspective. The performance of the financial perspective has increased every year while the performance of non-financial perspective can be considered good but still needed improvement in some aspects.  Keywords: Balanced Scorecard, Performance Measurement, Financial Perspective,    Customer Perspective, Internal Business Process Perspective, Learning and Growth Perspective